2022
DOI: 10.1016/j.jcot.2022.101773
|View full text |Cite
|
Sign up to set email alerts
|

Knee intra-articular administration of stromal vascular fraction obtained from adipose tissue: A systematic review

Abstract: Osteoarthritis is a debilitating chronic degenerative disease of cartilage joint surfaces and the knee is the weight-bearing joint most frequently plagued. Intra-articular cell therapies have recently emerged as a method to manage knee osteoarthritis. A literature search identifying all articles involving use of SVF to treat knee osteoarthritis was performed, consulting several databases. In conclusion, 24 clinical trials analysed report good to excellent clinical and radiographic results for the treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…A recent work showed that patients treated at earlier‐degeneration stages reported statistically significant improvements in VAS, WOMAC and walking distance [22]. Similarly, several recent systematic reviews and meta‐analysis reported favorably on the use of MSCs [1]. Wiggers et al found a positive effect of autologous MSC therapy compared with control treatments on patient‐reported outcome measures, and disease severity [29].…”
Section: Discussionmentioning
confidence: 99%
“…A recent work showed that patients treated at earlier‐degeneration stages reported statistically significant improvements in VAS, WOMAC and walking distance [22]. Similarly, several recent systematic reviews and meta‐analysis reported favorably on the use of MSCs [1]. Wiggers et al found a positive effect of autologous MSC therapy compared with control treatments on patient‐reported outcome measures, and disease severity [29].…”
Section: Discussionmentioning
confidence: 99%
“…As much as 90 mL of lipoaspirate is typically obtained through the liposuction process. Recent clinical studies have revealed that SVF provides functional improvements and pain relief for 6 to 24 months compared with a placebo 28 . The consensus is that the previously mentioned biological agents have a favorable safety profile with a low risk of adverse reactions.…”
Section: Cell Therapymentioning
confidence: 99%
“…The SVF has proven its effectiveness in the treatment of various diseases. A number of studies have confirmed its beneficial effect on osteoarthritis, both when used independently and in combination with other components, such as PRP ( 17 - 24 ). The SVF is actively used in aesthetic medicine: in rejuvenation procedures ( 25 ), as well as for the clinical treatment of various forms of alopecia ( 26 , 27 ) and acne ( 28 ).…”
Section: Introductionmentioning
confidence: 95%